2004
DOI: 10.2355/isijinternational.44.153
|View full text |Cite
|
Sign up to set email alerts
|

Re-dissolution of VN during Tempering in High Chromium Heat Resistant Martensitic Steel

Abstract: Precipitation behavior of VN during isothermal tempering at 740-800°C of 7%Cr-0.4%V-0.09%N steel (% denotes mass%, hereinafter) has been studied. Initially, rapid softening takes place accompanied by the precipitation of VN and, after that, the quasi-steady state in a hardness vs. tempering time diagram is continuing for a while. After the quasi-steady state, re-dissolution of VN particles rapidly occurs followed by final precipitation of VN. Just before the peak time of the re-dissolution of VN particles, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…However, Tamura et al have found that MC can dissolve at first and then precipitate again during long-term aging. 14,15) In a word, dissolution of MC into matrix maybe occurred temporarily after 10 hours tempering.…”
Section: Dissolution Of MCmentioning
confidence: 99%
“…However, Tamura et al have found that MC can dissolve at first and then precipitate again during long-term aging. 14,15) In a word, dissolution of MC into matrix maybe occurred temporarily after 10 hours tempering.…”
Section: Dissolution Of MCmentioning
confidence: 99%
“…In this case, the authors presented evidences of a process of dissolution of the fine NbC particles during the early stages of tempering, which would be reprecipitated after a long tempering exposure. Moreover, in a very recent study 84) the same team proposed a mechanism to account for that redissolution in the case of Cr-V model alloys. On the other hand, our own EDX-STEM composition measurements on Ta-rich particles in the as-received state of the Eurofer97 alloy 85) turned out to be much more closer to the predicted composition values for the temperature of 1 050°C, suggesting that these precipitates are effectively far from equilibrium after 1 h tempering at 760°C.…”
Section: The Problem Of Ta In Solid Solution In Temperedmentioning
confidence: 99%
“…Kubon et al [50] supported the idea proposed by Lundin et al [45,46] Such dynamical interactions of dislocations with constituent elements of MX are not a rare case; sequential events of precipitation on dislocations, energetic destabilization of the precipitated particles through the breaking away of dislocations, and the subsequent dissolution of precipitated particles are well recognized in the tempering of high-Cr heat-resistant steels. [51][52][53][54] These phenomena can be explained thermodynamically, and therefore, besides the MX particle, fine particles of not only ecarbide [55] and M 23 C 6 [56] but also even the stable oxide Y 2 Ti 2 O 7 [57] have been found to be easily dissolved in interactions with dislocations. [58] That is, it is clear that when we discuss the creep deformation of heat-resistant steel, we should take the local equilibrium around mobile dislocations into account, and microstructural considerations based on a simple thermal equilibrium and/or kinetic simulation are insufficient.…”
mentioning
confidence: 99%